Cardiovascular health effects following exposure of human volunteers during fire extinction exercises - Maria Helena Guerra Andersen; Anne Thoustrup Saber; Peter Bøgh Pedersen; Steffen Loft; Åse Marie Hansen; Ismo Kalevi Koponen; Julie Elbæk Pedersen; Niels Ebbehøj; Eva-Carina Nørskov; Per Axel Clausen; Anne Helene Garde; Ulla Vogel; et al. (BMC, 2017)
Abstract Background Firefighters have increased risk of cardiovascular disease and of sudden death from coronary heart disease on duty while suppressing fires. This study investigated the effect of firefighting activities, using appropriate personal protective equipment (PPE), on biomarkers of cardiovascular effects in young conscripts training to become firefighters. Methods Healthy conscripts (n = 43) who participated in a rescue educational course for firefighting were enrolled in the study. The exposure period consisted of a three-day training course where the conscripts participated in various firefighting exercises in a constructed firehouse and flashover container. The subjects were instructed to extinguish fires of either wood or wood with electrical cords and mattresses. The exposure to particulate matter (PM) was assessed at various locations and personal exposure was assessed by portable PM samplers and urinary excretion of 1-hydroxypyrene. Cardiovascular measurements included microvascular function and heart rate variability (HRV). Results The subjects were primarily exposed to PM in bystander positions, whereas self-contained breathing apparatus effectively abolished pulmonary exposure. Firefighting training was associated with elevated urinary excretion of 1-hydroxypyrene (105%, 95% CI: 52; 157%), increased body temperature, decreased microvascular function (−18%, 95% CI: -26; −9%) and altered HRV. There was no difference in cardiovascular measurements for the two types of fires. Conclusion Observations from this fire extinction training show that PM exposure mainly occurs in situations where firefighters removed the self-contained breathing apparatus. Altered cardiovascular disease endpoints after the firefighting exercise period were most likely due to complex effects from PM exposure, physical exhaustion and increased core body temperature.